Quantitative Analysis of Liquid by Quick Freezing Into Ice Using Nd-YAG Laser-Induced Atmospheric Plasma - Yulianto Ichwan, Mohamad Infrawan; Suyanto, Hery; Suliyanti, Maria Margaretha; Hedwig, Rinda; Pardede, Marincan; Kagawa, Kiichiro; Lie, Tjung Jie; Kurniawan, Koo Hendrik (Journal of Engineering and Technological Sciences, 2005)
A new approach of quantitative analysis of liquid sample using laser ablation technique was developed. The liquid was immediately freezed using the mixture of dry ice and alcohol in weight ratio of 95% : 5%. As a result, an increase of the repulsion force from the sample surface will enable the generation of the laser-induced shock wave plasma which was difficult to carry out on liquid surface. The ice sample was then irradiated using Nd-YAG laser operated in its fundamental wavelength. In order to increase the signal to background ratio and to obtain a sharp atomic line spectra, helium gas was used instead of air. Dynamic characterization of the spatially integrated time profile of the Cu I 521.8 nm, Cu I 510.5 nm and HÎ± lines shows a shock excitation stage and cooling stage which is corresponded to our shock wave model even when the plasma was generated under atmospheric gas pressure. Further study of the time profile averaged temperature of the atmospheric plasma also shows an increase of temperature during the shock excitation stage followed by diminution of temperature during the cooling stage. An application of this technique was then applied to quantitative analysis of several liquid samples. A linear calibration curve which intercept at 0 point was obtained for all of the elements investigated in this study such as sodium, potassium, lithium, copper, silver, lead and aluminum. A detection limit of around 1 ppm was found for the above element. This new technique will contribute to a great extent of laser atomic emission spectrochemical analysis for liquid samples.